Pemahaman Terhadap Larangan Larangan yang Ada di Wisata Kampung Adat Cirendeu - Rai Thoriq Azhar; Rakha Farassya Nurzaky (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
The writing of this article was carried out to show and provide education to tourists about what is in the Cirendeu traditional village and what prohibitions there are in the Cirendeu traditional village, so that it can be used as a tourist attraction in Cimahi for tourists. By using the observation method, searching for online-based data and information and also conducting research directly by visiting the Cirendeu traditional village. The Cirendeu traditional village has cultural and artistic values that are still present in their lives. By conducting this research, we hope that tourists will realize and care more about how important it is to maintain the natural beauty and cultural values in a tourist destination. Cireundeu Traditional Village is one of the Tourist Attractions (DTW) in the cultural aspect and is the only traditional village that applies the tourist village concept in Cimahi City. Cireundeu Traditional Village has a variety of potential, but has not been managed and developed well so it has not yet become a sustainable tourism destination. Thus, this article will analyze the various potentials as well as the shortcomings and weaknesses of the Cireundeu Traditional Village, so that the strategy for developing this tourist village can be known.